Comparison between Different Queue Management Techniques in Mobile Ad-Hoc Network: A Survey - Kumar Sahu, Prabhat; Mahapatro, Susrita; Kumar Dash, Pradeep (International Journal of Engineering and Technology, 2018)
The world is running in a lightning speed with the rapid up gradation of technology. In fraction of second human civilization experiences a unique set of technologies and for this human sentiment started to demand better quality of service in almost all the areas which provides ease to it by minimizing human work efforts. Communication becomes an integral part of this rapidly changing technology.Â From the introduction of internet, the taste and preferences of virtual communication has been changed. A new technology called as Mobile Ad Hoc Network (MANet) is also getting its popularity due to its infrastructure less and mobility property. The rapid increase in demand for use of MANets tends it to further development to provide better quality of service. However Congestion in these networks creates a challenge to achieve desired Quality of Service. Different Queue Management techniques such as Passive and Active Queue management techniques are used to minimize the congestion in these networks which uses the concept of managing the buffers though algorithms. The Passive Queue Management technique Droptail, in the introduction stage, somehow manages to increase its efficiency. However in later stage, when data traffic increases, due to global synchronization problem many other algorithms including active queue management techniques such as RED and variants, REM have been developed to increase the efficiency by decreasing the congestion. The concepts even travel from congestion control to congestion avoidance. In this paper we have taken into account different passive and active queue management techniques and compared them based on our literature review to find out the best among them by considering different situations.